The Role of Islamic Boarding School Strategy in Economic Empowerment for Santri at the Darul Ma'rifat Islamic Boarding School - Nasution, Yenni Samri Juliati; zainarti, zainarti; Rambe, Meisyah (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2024)
Islamic boarding schools in Indonesia, which number in the thousands, actually have enormous potential in the economic sector. However, the potential of Islamic boarding schools has not been given much attention, either by the government or the Islamic boarding schools themselves. The number of Islamic boarding schools in North Sumatra is 183, one of which is the Dar Ma'rifat Islamic Boarding School in Kelambir Lima Village, Hamparan Perak Village, Deli Serdang Regency. So that the economic empowerment of Islamic boarding schools greatly contributes to improving the welfare of the people of North Sumatra in general and the Islamic boarding school students in particular. This community service provides significant benefits for the students and female students of the Darul Ma'rifat Islamic Boarding School. To achieve a better and more sustainable impact, further efforts need to be made in providing education, mentoring and support in the strategic role of Islamic boarding schools in economic empowerment for students at the Darul Ma'rifat Islamic Boarding School, Kelambir Lima Village, Hamparan Perak Village, Deli Serdang, especially in financial management towards independent Islamic boarding school.